Valorization of Napier grass via intermediate pyrolysis: Optimization using response surface methodology and pyrolysis products characterization - Yusup, Suzana (2017)
This study presents first optimization report on pyrolysis oil derived from Napier grass. Effects of temperature, heating rate and nitrogen flow rate on the intermediate pyrolysis of Napier grass biomass in a vertical fixed-bed tubular reactor were investigated collectively.